1996
DOI: 10.1021/np960551w
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Cycloartanes from Borrichia frutescens

Abstract: In a bioassay-guided search for antimycobacterial compounds from higher plants of the southeastern United States, we have chemically investigated the sea daisy (Borrichia frutescens) from coastal marshes of Louisiana for their active constituents. Bioactive chromatographic fractions provided two new triterpenes, (24R)-24,25-epoxycycloartan-3-one (1) and (23R)-3-oxolanosta-8,24-dien-23-ol (4), and (3 alpha H, 24R)-24,25-epoxycycloartan-3-ol (3a). Compound 3a had been previously isolated as a mixture of C-24 epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 16 publications
1
86
0
Order By: Relevance
“…All of the isolates obtained from Q. majus along with 11 analogues were evaluated for their potential to inhibit the growth of M. tuberculosis and African green monkey Vero cells, respectively, according to established protocols (Collins and Franzblau, 1997;Cantrell et al, 1996). The results (Table I) showed that three common triterpenes, betulinic acid (1), oleanolic acid (4) and ursolic acid (6), along with the flavanone 5 exhibited significant inhibitory activity in a microplate alamar blue assay with MIC values of 62, 30, 31, and 90 µg/ml, respectively, while the other two isolates 2 and 3 were inactive (MIC > 128 µg/ml).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the isolates obtained from Q. majus along with 11 analogues were evaluated for their potential to inhibit the growth of M. tuberculosis and African green monkey Vero cells, respectively, according to established protocols (Collins and Franzblau, 1997;Cantrell et al, 1996). The results (Table I) showed that three common triterpenes, betulinic acid (1), oleanolic acid (4) and ursolic acid (6), along with the flavanone 5 exhibited significant inhibitory activity in a microplate alamar blue assay with MIC values of 62, 30, 31, and 90 µg/ml, respectively, while the other two isolates 2 and 3 were inactive (MIC > 128 µg/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of cytotoxicity of the CH 2 Cl 2 -soluble extract and pure compounds was performed as a modification of an established protocol (Cantrell et al, 1996). In brief, test compounds were dissolved at 10Ð40 mg/ml in DMSO.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…16) After 72 h exposure, cell viability was measured using the CellTiter 96 aqueous non-radioactive cell proliferation assay. The IC 50 is defined as the reciprocal dilution resulting in 50% inhibition of the Vero cells.…”
Section: Methodsmentioning
confidence: 99%
“…Caldwell and coworkers showed that OA isolated from Argentinean shrub, Junella tridens (Verbanaceae) was active against M. tuberculosis H37Rv [36]. The MIC of OA determined using a BACTEC radiospirometric assay [37] was 50 mg mL -1 (Table 1). OA-derivatives, oleanonic acid and 3-epi-oleanonc acid, were three-fold more active.…”
Section: Antibacterial Activity Of Oa and Its Derivativesmentioning
confidence: 99%